An Assessment of the Short Term Impact of the ECOWAS-CET and EU-EPA in Senegal - Marchat, Jean-Michel; von Uexkull, Erik (World Bank, Washington, DC, 2016)
In recent years, there have been major changes in the trade policy landscape in West Africa that will affect Senegal. The Common External Tariff (CET) for (ECOWAS) and European Union-Economic Partnership Agreement (EU-EPA) have generated an intense debate among policy makers, interest groups and the general population. The CET aims at the establishment of a customs union for ECOWAS countries through ‘the adoption of a common external tariff and a common trade policy vis-à-vis third countries.’ It was adopted at a Heads of State Summit in October 2013 in Dakar and is to be implemented from 2015. When initially designed in the mid-2000s, the CET was organized in four tariff bands: 0 percent for essential social goods, 5 percent for goods of primary necessity, raw materials and specific inputs, 10 percent for intermediate goods and 20 percent for final consumption goods. Since then, Nigeria has obtained the introduction of a fifth band at 35 percent for ‘specific goods for economic development’ (essentially agricultural goods and some consumer goods). The first section of the paper presents an analysis of the impact of the CET and EU-EPA on protection levels, trade flows and state revenues, changes in the price of the consumption bundles for households and impact on firm’s profits. The second section underlines some key elements of an accompanying policy agenda and a third section concludes.